The effect of customers’ perceived value of retail store on relationship between store attribute and customer brand loyalty: some insights from Malaysia - Haque, A. K. M. Ahasanul (2015)
Abstract Customer brand loyalty has been an important area for practitioners in retailing industry due to various developments in the increasingly competitive environment. The objective of the current study is to identify the role of perceived value of the store brand in relationship between store attributes and customer brand loyalty. A self-administered questionnaire was used to collect data (n=418), from the customers visiting hypermarkets such as Tesco, Aeon Big, Mydin and Giant’s in metropolitan Kuala Lumpur, Malaysia. Structural Equation Modeling is employed to analyze the data. The results demonstrate that store attribute has a direct effect on customers’ perceived value as well as on their loyalty with the store brand. The store attribute also has an indirect effect on store brand loyalty via customers’ perceived value of the store brand. The study recommends hypermarkets to understand customers’ perception towards their brand in order to develop better marketing strategy which can enable them differentiate themselves from competitors.